THU0098 Combination therapy of rapamycin and a glutamine antagonist facilitates the expansion of myeloid-derived suppressor cells and ameliorates arthritis in skg mice. (12th June 2018) - Ueda, Y.; Saegusa, J.; Okano, T.; Sendo, S.; Yamada, H.; Ichise, Y.; Naka, I.; Takahashi, S.; Akashi, K.; Onishi, A.; Morinobu, A.
Abstract : Background: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature cells that increase in the pathological state such as tumour or inflammation and have the immunosuppressive ability. MDSCs have been reported to ameliorate arthritis in several mice models. Mechanistic target of rapamycin (mTOR) pathway and glutaminolysis activate cooperatively in the differentiation from myeloid progenitors to mature myeloid cells such as dendritic cells, macrophages, or osteoclasts as well as the activation of effector T cells and the differentiation of Th1 and Th17 cells. Although rapamycin has reported to facilitate the expansion of MDSCs and their immunosuppressive ability, the effect of the inhibitor of glutaminolysis on MDSCs is still unknown. Objectives: The aim of this study is to evaluate the facilitative effects of the inhibition of mTOR pathway and glutaminolysis on MDSCs in a mouse model of rheumatoid arthritis. Methods: Bone marrow (BM) cells from untreated Balb/c mice were cultured for 5 days under granulocyte–macrophage colony-stimulating factor (GM-CSF) stimulation with four patterns of drugs; 1) DMSO (control), 2) rapamycin (Rapa), 3) 6-Diazo-5-oxo-l-norleucine (DON; a glutamine antagonist), or 4) the combination of rapamycin and DON (Rapa +DON). Cultured BM cells were analysed by flow cytometry. Cultured MDSCs were isolated by manual MACS and analysed their immunosuppressive characters by co-culture with CFSE-dyed CD4 + T cells. Rapa or Rapa +DON were administered intraperitoneally to arthritic SKG mice induced by Zymosan A injection. Results: We found that DON suppressed the differentiation of dendritic cells (DC) in a dose-dependent manner and the addition of Rapa on DON inhibited the differentiation of macrophages in vitro. The proportions of the phenotype of MDSCs were increased with administrations of Rapa or DON, and large part of them were Ly6G + cells (the phenotype of polymorphonuclear MDSCs; PMN-MDSCs). Rapa ±DON significantly increased the expressions of TGF-β and PD-L1 and the inhibitory capacity of Ly6G + PMN-MDSCs. Rapa +DON significantly suppressed arthritis more efficiently in SKG mice than Rapa in vivo . (see figure 1) Conclusions: The combination of rapamycin and a glutamine antagonist facilitates the expansion of PMN-MDSCs in vitro and ameliorates arthritis in SKG mice in vivo . Disclosure of Interest: None declared